Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The degree of availability of administrative excellence standards among school principals at Tafila Governorate from the teachers’ perspectives Dr. Hani Ahmad Alkriameen 2. The degree of employing blended learning from the perspectives of principals and teachers of Palestinian public schools in the Nablus district Dr. Sherine Adnan Hashaika, Prof. Afnan Nazeer Darwazeh 3. Effectiveness of Animated Films on Language Development in Early Childhood from the Mothers’ Point of View Mrs. Ashwaq Alloush Saud Al-Dawish 4. Differences in Visual Perception Skills between Reading Disabilities and Low Achievement Primary Student in the Kingdom of Bahrain Dr. Zainab A. Albannai 5. The challenges faced by kindergarten teachers with distance education under the Corona pandemic Mrs. Fatimah Ali Al-Harbi 6. University Violence and its Relationship to Irrational Ideas and Methods of Family Upbringing Among a Sample of Palestinian University Students (Al-Quds Open University as a Model) Dr. Mai Hassan Atiya , Dr. Saeeda Muhammad Abu Shakra 7. The Anxiety Caused by the COVID-19 Pandemic on a Sample of High School Students in Public Education in Jeddah after Returning Back to School: Case Study Mrs. Norah Dakhilallah Alsubaie, Mrs. Hafsa Saleh Almudhi, Dr. Alaa Ibrahim Kutbi 8. The Influence of Irrational Thinking and Social Networks on Citizenship Values for Undergraduate Students in Sultanate of Oman Dr. Moosa Sulieman Al- Shuaili